Combating Poverty and Social Exclusion in European Union Law (Routledge, 2022)
This book examines the potential role of European Union law in combating poverty and social exclusion in the European Union. Anti-poverty strategies have been part of the European Union agenda for decades. Most saliently, over a decade ago, the EU's Member States pledged to lift 20 million people out of poverty. In spite of this commitment, the EU did not even meet a quarter of this target, and over 113 million people still were at risk of poverty and social exclusion by the end of 2020. This book addresses the incongruence between a quite developed EU policy strategy and a well-embedded legal objective on the one hand, and the lack of direct legal action on the other. Analysing the role of social policy instruments, fundamental rights, and the constitutional framework of the European Union, it makes a detailed case for a contribution of EU law to the policy objective of combating poverty and social exclusion. Drawing on work in law, politics, social policy and economics, this book will interest scholars and policymakers in the areas of EU law, labour and social security, human rights, political science and social and public policy.
Keywords: 340; EU Level; European Semester; EU Institution; Member States; EU Social Policy; Fundamental Social Rights; EU Legal Instrument; Social Protection Systems; EU Instrument; Minimum Income Schemes; Headline Target; Reference Budgets; EU Law; In-work Poverty; EU Value; EU Legislator; Minimum Income; Integrated Guidelines; Minimum Income Benefits; EU Primary Law; EU Priority; EU Legal Act; Union's Policy Objective; Generation EU; Implement EU Law